The Effect of Management Support and Service Quality on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Inti Hidup Sejahtera - Febri Adityanata; Dheo Rimbano; Surajiyo Surajiyo (CV. Proaksara Global Transeduka, 2025)
This study examines the effect of management support and service quality on employee performance, with job satisfaction as an intervening variable at PT Inti Hidup Sejahtera. A quantitative approach with an associative design was employed, involving a population of 35 employees selected using simple random sampling. Primary data were collected through a questionnaire survey and analyzed using statistical methods.The findings indicate that management support has a positive and significant effect on employee performance through job satisfaction as an intervening variable, with a specific indirect effect of 0.237, a t-statistic of 2.163, and a p-value of 0.031 (<0.05). This confirms that job satisfaction mediates the relationship between management support and employee performance. Conversely, service quality has a positive but insignificant effect on employee performance through job satisfaction, with a specific indirect effect of 0.686, a t-statistic of 1.564, and a p-value of 0.118 (>0.05). This suggests that job satisfaction does not effectively mediate the relationship between service quality and employee performance.Overall, these findings highlight the critical role of management support in improving employee performance through job satisfaction, while service quality alone does not significantly contribute to employee performance via job satisfaction.